Consumo de álcool e consequências à saúde: diferenças sociais no Brasil - Ísis Eloah Machado (2017)
According to evidences, alcohol consumption and vulnerability to alcohol-related consequences diverge in social groups, such as those defined by gender, age, race, and socioeconomic status. The aim of this study was to analyze alcohol consumption and alcohol-related health consequences and its relation with sociodemographic factors in Brazil. Methods: This is a cross-sectional and time-series study using secondary data from the National Health Survey (PNS), Risk and Protective Factors Surveillance System for Chronic Diseases by Telephone Survey (Vigitel), Mortality Information System (SIM) and Violence and Accidents Surveillance System (VIVA). We analyzed the relation between current alcohol use and binge dinking, according to sociodemographic characteristics, as well as the time-series of these outcomes. We also analyzed mortality due to alcohol trends and the relation among alcohol use, sociodemographic factors and injuries severity. Results: In 2013, the prevalence of current alcohol use was 26.5% and the prevalence of binge dinking was 13.7%. The prevalence of these two outcomes was twice as high in men as in women. Younger, black and brown skin color groups were associated with greater episodic excessive alcohol use in both sexes. There was an increase in binge drinking in men aged 18 to 24 years, and in women in the 25 to 34, 55 and older age groups and in the color of white skin. Between 2000 and 2013, almost 400,000 deaths attributable and/or associated to alcohol use were recorded. We found an increasing trend, especially among brown skin color and the extreme age groups: young and elderly. Alcohol was a risk factor for severe injuries and 13.5% of men and 5.5% of women attended in emergency services had consumed alcohol. Conclusion: Men, young adults and those with high schooling presented high alcohol use. However, elderly, those with low schooling and blacks suffer more from alcohol related harm. Interventions that consider differences in alcohol consumption, sociodemographic context and more vulnerable groups are essential to reduce existing inequalities.